Near optimal factorization of Boolean functions - Caruso, G. (IEEE transactions on computer-aided design of integrated circuits and systems, 1991)
An algorithm for algebraic factorization of single-output functions is presented. The algorithm is based on the generation of some products covering a set of true cubes suitably chosen. The products forming a near-optimal factored expression are locally chosen from the ones covering each of those cubes. In order to obtain a good factorization, heuristics are used in the three procedures of which the method is composed. The algorithm is compared to a QUICK-FACTOR-like algorithm, using a large set of randomly generated functions. and it provides good results.< >